1999
DOI: 10.1006/viro.1999.9897
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the SH3-Binding Region of HIV-1 Nef: Partial Functional Defects Introduced by Mutations in the Polyproline Helix and the Hydrophobic Pocket

Abstract: An SH3-binding domain within the Nef protein of primate lentiviruses has been reported to be important to viral replication and infectivity and dispensable for CD4 downregulation, but its precise role remains unclear. This study investigates the effects of mutations in both the polyproline helix and in the hydrophobic pocket that constitute the SH3-binding domain of Nef. The data demonstrate that the well-studied mutation of the central prolines is only partially disruptive to viral infectivity and replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
5
17
1
Order By: Relevance
“…3C). The PP 72,75 AA mutation significantly impaired infectivity enhancement by Nef in one study (25), but had only a 2-fold effect in another study (34), in agreement with our results (Fig. 3C).…”
Section: Nef Mutants Defective For Dyn2 Binding Lack Infectivity Enhasupporting
confidence: 91%
“…3C). The PP 72,75 AA mutation significantly impaired infectivity enhancement by Nef in one study (25), but had only a 2-fold effect in another study (34), in agreement with our results (Fig. 3C).…”
Section: Nef Mutants Defective For Dyn2 Binding Lack Infectivity Enhasupporting
confidence: 91%
“…Multiple functions of Nef, including CD4 downregulation and interaction with cellular signaling pathways, are important for optimal HIV replication in activated PBMC and CD4 ϩ primary T lymphocytes (18,29,43,60,72). Although the large defects in the infectivity and gp120 content of X4-tropic, Nef-defective HIV virions produced in primary T cells likely result from the incapacity of these viruses to downregulate cell surface CD4, it is entirely possible that the absence of another function of Nef is responsible for these defects.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…It has been reported that binding of the SH3 domains of either c-Src or Hck to Nef has a major impact on the conformation of the N-terminal anchor domain of Nef (5). Thus, the polyproline domain in Nef may have an important structural role that could also affect protein stability (36). Because higher Nef levels are required for Nef to affect MHC-I compared with CD4 (96), structural defects may affect these activities differently.…”
Section: Other Cellular Factorsmentioning
confidence: 99%